2013
DOI: 10.1128/jcm.01407-13
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics of Cytauxzoon felis Cytochrome b : Implications for Atovaquone and Azithromycin Therapy in Domestic Cats with Cytauxzoonosis

Abstract: bCytauxzoon felis, an emerging virulent protozoan parasite that infects domestic cats, is treated with atovaquone and azithromycin (A&A). Atovaquone targets parasite cytochrome b. We characterized the C. felis cytochrome b gene (cytb) in cats with cytauxzoonosis and found a cytb genotype that was associated with survival in A&A-treated cats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Cytauxzoon felis cytb genotypes had been previously characterized using bidirectional sequencing. Any secondary nucleotide peaks present at a height of Ն30% of the primary nucleotide peak height on DNA sequence chromatograms were detected by a computer program and denoted using IUPAC ambiguity codes (Vector NTI; Invitrogen, Grand Island, NY) (22).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Cytauxzoon felis cytb genotypes had been previously characterized using bidirectional sequencing. Any secondary nucleotide peaks present at a height of Ն30% of the primary nucleotide peak height on DNA sequence chromatograms were detected by a computer program and denoted using IUPAC ambiguity codes (Vector NTI; Invitrogen, Grand Island, NY) (22).…”
Section: Methodsmentioning
confidence: 99%
“…In related parasites, mutations in the putative atovaquone-binding site of cytb have been associated with responses to A&A treatment (19)(20)(21). A recent study identified a C. felis cytb genotype (cytb1) that was associated with increased survival rates in cats treated with A&A (22). Cats that were infected with this genotype (cytb1) and were treated with imidocarb dipropionate, which does not target cytb, did not have a significantly improved survival rate compared to imidocarb dipropionate-treated cats infected with non-cytb1 genotypes (22).…”
mentioning
confidence: 99%
See 3 more Smart Citations